Separation Method of Impulsive Fault Component for Gasoline Engine Based on Acoustic Signal Analysis - Ning Dayong; Jiang Yuhua; Sun Hongyu; Zhang Zengmeng; Gong Yongjun; Chen Shengtao; Hou Jiaoyi (Shock and Vibration)
This paper presents a developed dislocation superimposed method (DSM) for automatically extracting the component of impulsive signals from abnormal noise signals of an engine at a single speed range on the basis of the initial DSM. This method consists of three steps: using a correlation analysis to select an appropriate starting superposition point, superimposing abnormal sound signals to improve the signal-to-noise ratio, and intercepting superimposed signals to separate the fault component. Experimental results show that the developed DSM can effectively extract the fault characteristics of cylinder knocking and connecting rod bearing knocking. The developed approach can be applied to separate the fault characteristics of other types of rotating machines.